Association of the inflammatory microenvironment of obesity with pathological complete response in patients with breast cancer receiving neoadjuvant chemotherapy - Yang, Dongxu; Ma, Keru; Wang, Hao; Liu, Yang; Du, Yuwei; Fang, Fang; Qin, Xuquan; Li, Dalin (Frontiers in Endocrinology, 2025)
BackgroundThe impact of the inflammatory microenvironment at different body mass index (BMI) on pathological complete response (pCR) in breast cancer (BC) patients receiving neoadjuvant chemotherapy (NAC) remains unclear.MethodsWe retrospectively analyzed 834 BC patients who received NAC, categorized into low-BMI (BMI < 25) and high-BMI (BMI ≥ 25) groups. We compared the differences in peripheral blood platelet count (P), lymphocyte count (L), neutrophil count (N), and monocyte count (M) using the Wilcoxon test. Additionally, we calculated the dynamic changes in these immune cells (ΔP, ΔL, ΔN, ΔM) based on hematological tests before and after NAC. Receiver operating characteristic (ROC) curves were used to assess the predictive value of peripheral immune cells for pCR. Logistic regression was used to identify independent risk factors associated with pCR. Finally, a nomogram was constructed based on multivariate logistic regression.ResultsAfter standardizing peripheral immune cells, before NAC, the P (P = 0.008), L (P < 0.001), N (P < 0.001), and M (P = 0.021) were higher in the high-BMI group compared to the low-BMI group. After NAC, the P (P = 0.015), L (P < 0.001), N (P < 0.001), and M (P < 0.001) were higher in the high-BMI group compared to the low-BMI group. Compared to before and after NAC, ΔP (0.661) had the highest AUC in predicting pCR for the low-BMI group, while ΔP (0.604), ΔL (0.610), and ΔM (0.607) had the highest AUC in predicting non-pCR for the high-BMI group. ΔP (OR = 3.372, 95% CI: 1.753-6.485, P < 0.001) was associated with non-pCR in the low-BMI group; ΔP (OR = 4.435, 95% CI: 1.745-11.267, P = 0.002), ΔL (OR = 0.180, 95% CI: 0.052-0.624, P = 0.007), and ΔM (OR = 2.267, 95% CI: 1.127-4.558, P = 0.022) were independent risk factors associated with non-pCR in the high-BMI group.ConclusionPeripheral immune cells in the inflammatory microenvironment at different BMI groups play an important role in predicting pCR in BC patients receiving NAC.